Reexamining Growth Effects: Are All Types of Asset Growth the Same? - Cao, Sean Shun (Contemporary Accounting Research, 2016)
Asset growth has been shown to be negatively associated with future returns. Cooper, Gulen, and Schill (2008) argue that an aggregation of all asset growth components as total asset ( TA ) growth leads to the strongest association with future negative returns. Based on their study, the literature now employs TA growth as an umbrella proxy for “the growth effect.” I hypothesize that not all types of growth imply negative future returns. Specifically, I show that growth financed by suppliers is positively associated with future performance and returns. Removing this growth component from TA growth makes it evident that the TA growth anomaly is simply a noisy manifestation of the net operating asset growth anomaly. Consequently, I suggest caution when using TA growth to control for the growth effect.